The key values and factors identified by older adults to promote physical activity and reduce sedentary behaviour using co-production approaches: a scoping review - Elysa Ioannou; Henglien Lisa Chen; Vicky Bromley; Sam Fosker; Khalid Ali; Avanka Fernando; Ekow Mensah; Sally Fowler-Davis (BMC Geriatrics, 2023)
Abstract Background Inactivity and sedentary behaviour in older adults adversely impacts physical function, reduces social networks, and could contribute to population healthcare costs. To encourage and support the planning and uptake of physical activity by older adults, it is important to understand what physical activity means to older adults. Therefore, the aim of this scoping review was to collate what older adults have self-identified as the key factors for sustaining and increasing their physical activities. Methods Arksey and O’Malley’s Scoping Review framework was used to guide the review process. SCOPUS, ASSIA, PsychINFO and MEDLINE databases were searched. Studies were eligible for inclusion if they were peer-reviewed, the target population were older adults (aged 55 and above), co-production related research approaches were explicitly stated in the methods and there was a focus on design of physical activity interventions or products to support or enhance physical activity. Assets and values important for physical activity were first extracted from included studies and were subsequently thematically analysed. Themes are presented to provide an overview of the literature synthesis. Results Sixteen papers were included in the analysis. Data from these papers were gathered via designing interventions or services (n = 8), products (n = 2), ‘exergames’ (n = 2) or mobile applications (n = 4). Outcomes were varied but common themes emerged across papers. Overarching themes identified by older adults were associated with a desire to increase activity when it was accessible, motivational, and safe. In addition, older adults want to enjoy their activities, want independence and representation, want to stay connected with families and friends, be outdoors, familiarity, activities to be tailored and resulting in measurable/observed progress. Conclusions Population demographics, personal attributes, and life experiences all affect preferences for physical activity. However, the key factors identified by older adults for increasing physical activity were common—even in separate co-production contexts. To promote physical activities in older adults, activities must fundamentally feel safe, provide a sense of social connectedness, be enjoyable and be accessible in terms of cost and ability.